Rock joint topography: three-dimensional scanning and numerical analysis - Resende, R.; Muralha, J.; Ramos, A. L.; Fortunato, E. (Géotechnique Letters, 2015)
Joints are the most defining features of fractured rock masses. It has been well established that joint behaviour is mainly defined by wall topography, which is difficult to measure and define. Previous works have employed both contact and non-contact scanning methods and multiple approaches to the analysis of rock surfaces, but a majority focused exclusively on individual surface characterisation without appraising wall–wall interaction. This paper presents an equipment that is easily available for laboratory scanning of rock joints. Surface topographies of eight granite rock joints (16 surfaces, made available to other researchers) are statistically analysed separately and jointly by applying a fitting algorithm to match the top and bottom surfaces that allow mapping and calculation of contact areas and void volumes during closure. Results show that traditional methods for joint profile analysis are not applicable to three-dimensional surfaces, and that often specific details of joint surfaces have opposing influence on the mechanical, dynamic or hydraulic behaviours.